2003
DOI: 10.1063/1.1625646
|View full text |Cite
|
Sign up to set email alerts
|

Self-induced oscillations in the shock wave flow pattern formed in a stationary supersonic flow over a double wedge

Abstract: Numerical simulations of a two-dimensional supersonic flow of an inviscid perfect gas over a double wedge in the Mach numbers range 5рM р9, revealed the existence of self-induced oscillations in the shock wave flow pattern in a narrow range of geometrical parameters.We consider a supersonic flow of an inviscid perfect gas over a double wedge ͑Fig. 1͒ in the range of high Mach numbers for which the shock waves are attached to the leading edges of both the first and the second wedges. The interaction of these tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…Numerical studies on the similar problem were conducted elsewhere. 2,3,6,9,10 However, the existence of an abnormal oMR͑InMR+ InMR͒ wave configuration, to the best of our knowledge, has never been reported until the present work. Figure 2 schematically shows the MR configuration for two shock waves of opposite families.…”
mentioning
confidence: 50%
See 1 more Smart Citation
“…Numerical studies on the similar problem were conducted elsewhere. 2,3,6,9,10 However, the existence of an abnormal oMR͑InMR+ InMR͒ wave configuration, to the best of our knowledge, has never been reported until the present work. Figure 2 schematically shows the MR configuration for two shock waves of opposite families.…”
mentioning
confidence: 50%
“…Related research can still be found in the recent literature. [2][3][4][5][6] In the present work, an abnormal MR configuration of asymmetric shock waves is computationally confirmed over a double-wedge geometry ͑Fig. …”
mentioning
confidence: 72%
“…high frequency over the wedge surface which can cause vital damages to the high-speed vehicles. 21,27 However, the oscillation phenomenon seems to be dependent on the numerical techniques and grid resolution. Wave configurations of oMR and oRR can alternate during an oscillation period in a previous computational study 27 where a W-modification of Godnuv's scheme and relatively coarse mesh were used.…”
Section: Computations On Rr^mr Transitionmentioning
confidence: 98%
“…It was found that hysteresis and self-induced oscillations in the shock flow pattern can result in extremely high and unsteady loads on the wedge surfaces. 21,27 Thermally nonequilibrium effects on the transition and the oscillation were reported by Hu et al 22 where the thermal properties of the components of air are temperature dependent. Advanced RR→ MR transition due to downstream influence has been first reported in a theoretical dual-solution regime.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation